Study on the Effect of Nano-SiO2 in ULSI Silicon Substrate Chemical Mechanical Polishing Process. (17th January 2007) - Yuling, Liu; Juan, Wang; Ming, Sun; Chenglin, Liu
Abstract : Both process and mechanical of silicon substrate chemical mechanical polishing (CMP) are studied in detail, and the effects of experiments designed indicate that nano-SiO 2 grinding particles seem to be acted as catalyzer besides the grinding action during the CMP process. This is different from the traditional function. As a result, in the condition of low pH, the nano-SiO 2 slurry can be recycled. In the meanwhile, the removal rate can gain stability and pH value does not change obviously.